Factors influencing the accountability of budgetary decision making by legislature: case study of local government in Indonesia / Mursal Salam Zulkarnaini - Zulkarnaini, Mursal Salam (2022)
The granting of local autonomy through fiscal decentralisation and local authority to Indonesian local governments based on Law Number 23 of 2014 is expected to provide flexibility to regions in carrying out local development to improve people's welfare. Improving the community's welfare can only be achieved if the local government has good financial performance because, without financial support, the development and implementation of public service activities to achieve increased public welfare will not be able to run smoothly. However, the facts in Indonesia show that the welfare of the people as measured by the Human Development Index (HDI) for all Local Governments in Indonesia increases an average by no more than 1% every year. In comparison, the realisation of regency or municipality revenue on average increases by more than 10% every year.